(untitled) (Indian Journal of Animal Production and Management, 2017)
Dairying is considered as the ever income supporting enterprise in India. High input cost results in less profits or losses in dairying. The present study was conducted at one of the successful women dairy cooperative in Telangana State to know the impact of socio economic and input variables on the profitability from dairying. The independent variables such as educational status, herd size, family members and landholding were positively and significantly correlated with milk production. The inputs were positively and significantly correlated with total milk production and income from milk in both member and non members groups. The coefficients of cost of dry fodder, concentrate and labour cost showed a positive and significant (P<0.01) relationship with cost of milk production, whereas cost of green fodder showed negative sign in member and non member groups. This shows that there is a scope to increase milk production and income from milk by augmenting the inputs and educating scientific management practices to the women dairy farmers.